2000
DOI: 10.1098/rspb.2000.1002
|View full text |Cite
|
Sign up to set email alerts
|

The mating consequences of sexual segregation within inflorescences of flowering plants

Abstract: Many co-sexual plants segregate female and male function among flowers on an inflorescence through dichogamy or the production of unisexual flowers. Sexual segregation may reduce self-pollination among flowers within inflorescences (geitonogamy), thereby increasing the pollen available for export to other plants. To assess these complementary roles we manipulated the simultaneously hermaphroditic (adichogamous) flowers of Eichhornia paniculata to produce ten-flowered inflorescences with either female above mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
146
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 31 publications
4
146
1
2
Order By: Relevance
“…Moreover, the potential for male^female interference is not limited to that occurring within £owers; it can act between £owers within in£orescences. Harder et al (2000) demonstrated in Eichhornia paniculata (Pontederiaceae) that female interference with male functions can take the form of inter£oral deposition of self pollen on stigmas, leading to pollen discounting. They employed £oral manipulations to show that dichogamy is e¡ective in reducing the transfer of self-pollen between £owers within in£or-escences, and hence male^female interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the potential for male^female interference is not limited to that occurring within £owers; it can act between £owers within in£orescences. Harder et al (2000) demonstrated in Eichhornia paniculata (Pontederiaceae) that female interference with male functions can take the form of inter£oral deposition of self pollen on stigmas, leading to pollen discounting. They employed £oral manipulations to show that dichogamy is e¡ective in reducing the transfer of self-pollen between £owers within in£or-escences, and hence male^female interference.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, female organs may knock freshly collected pollen o¡ a retreating pollinator, or self-pollen deposition may reduce the access of outcross pollen to ovules (Galen et al 1989;Waser & Price 1991;Broyles & Wyatt 1993;Dinne¨tz 1997;Sage et al 1999). Finally, if interference by the stigma reduces the £ower's ability to export pollen to others, then a reduction in hercogamy that increases the sel¢ng rate might also increase interference, causing a loss of male outcrossing success, a phenomenon known as pollen discounting (Holsinger et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental work has addressed this question by determining the mating consequences of the sexual segregation that characterizes synchronized protandry (Harder et al 2000;Routley & Husband 2003). In this common form of dichogamy the vertical inflorescence is the reproductive unit and protandrous flowers mature sequentially from the bottom to the top of the inflorescence.…”
Section: Adaptive Floral Design and Displaymentioning
confidence: 99%
“…Generalmente las de aparición temprana son las fl ores masculinas y las tardías son las femeninas, lo cual favorece la xenogamia. Se propone que en esta especie, algunos individuos producen sólo fl ores femeninas, como respuesta a un ambiente con abundante polen (producido por otros individuos), lo que sugiere que este tipo de infl uencia ambiental puede ser un factor básico para entender la evolución de los sistemas reproductivos en plantas (Harder et al, 2000), en particular en B. gracilis (Castillo-Gámez, 1999;Castillo et al, 2002;López y Domínguez, 2003).…”
Section: Discussionunclassified